Scribner's Magazine. (New York City : Charles Scribner's Sons, 1887)
Scribner's Magazine was an American periodical published by the publishing house of Charles Scribner's Sons from January 1887 to May 1939. Scribner's Magazine was the second magazine out of the Scribner's firm, after the publication of Scribner's Monthly. Charles Scribner's Sons spent over $500,000 setting up the magazine, to compete with the already successful Harper's Monthly and The Atlantic Monthly. Scribner's Magazine was launched in 1887, and was the first of any magazine to introduce color illustrations. The magazine ceased publication in 1939.The magazine contained many engravings by famous artists of the 19th and early 20th centuries, as well as articles by important authors of the time, including John Thomason, Elisabeth Woodbridge Morris, Clarence Cook, and President Theodore Roosevelt.The magazine had high sales when Roosevelt started contributing, reaching over 200,000, but gradually lost circulation after World War I. (Wikipedia)
Https://en.wikipedia.org/wiki/Scribner%27s_Magazine
Online: https://archive.org/stream/scribnersmagazin08newy https://catalog.hathitrust.org/Record/000505912
Engels
Tijdschriften